A Critical Discourse Analysis of President Prabowo Subianto’s Political Speech to the Turkish Parliament - Muhammad Hafiz Alfianyah Alfianyah; Suswanto Ismadi Megah; Sri Sugiharti (UIN Salatiga, 2025)
This study aims to critically analyze the ideological messages conveyed by the President Republic of Indonesia, Mr.Prabowo Subianto. Political speeches are powerful tools that leaders use to express their ideas, show their leadership style, and influence public opinion. In this study, the focus is on a speech delivered by the President of Indonesia, Prabowo Subianto, in front of the Turkish Parliament in early 2025. The speech is seen as a reflection of his early foreign policy direction and his efforts to build Indonesia’s image on the international stage, especially in its relationship with Turkey. This research aims to explore the ideological messages in that speech. Using a qualitative descriptive approach which applies Norman Fairclough’s Critical Discourse Analysis (CDA) model, and to support the analysis researcher will use the transitivity method from Systemic Functional Linguistics (SFL), This method helps break down the functions of each sentence to understand how language is used to shape meaning, show power, and express political ideas. The main focus is on how the speech builds certain messages about Indonesia’s national identity, political direction, and position in the world. The study also tries to understand what kinds of power relations are hidden in the political language and what social or political effects the speech might have. Through this analysis, the research hopes to give deeper insights into how language can be used not just to inform, but also to influence, persuade, and shape public thinking at a national and global audience.